Reflection of the image of a woman in English paremiology: analysis based on a gender approach - Rahimova, Munira (The Lingua Spectrum, 2025)
This article is aimed at analyzing the formation of the image of a woman through English proverbs and the manifestation of gender stereotypes in the paremiological worldview. The study modeled how stereotypical perceptions of women are reflected in the English paremiological system and studied the expression of the image of femininity in linguistic means and national-cultural features. These proverbs mainly express ideas about the role of women in society, their merits and shortcomings. In English proverbs, the national-cultural features of the female image often reflect the values and stereotypes of patriarchal society. At the same time, they help to understand the role of women in social life and changes in society. The article shows that the image of a woman is portrayed in a contradictory way through positive and negative qualities. The results of the analysis show that negative ethnotypic features prevail in English proverbs, which indicates a high level of androcentrism. It has also been established that the image of a woman is often interpreted on the basis of an instrumental approach, that is, from the point of view of profit. This research serves a deeper understanding of the formation of the image of a woman in English paremiology based on a gender approach.